Central Bank Digital Currencies and Monetary Stability: A Policy-Oriented Review of Global Regulatory Frameworks - Nabila Tijani Tharifah; Muttorik Alil Abasir (Capitalis: Journal of Economic Stability, Banking, and Investment, 2026)
This study examines the relationship between Central Bank Digital Currencies (CBDCs) and monetary stability through a structured, policy-oriented review of global regulatory frameworks. Adopting a non-empirical conceptual–analytical approach, the research integrates doctrinal regulatory analysis with systematic literature synthesis to construct an interpretative framework linking CBDC design architecture, banking intermediation safeguards, and cross-border macroprudential coordination to stability outcomes. Comparative institutional mapping across advanced, emerging, and developing economies reveals that monetary stability is conditioned by regulatory calibration rather than technological form. Retail CBDC models incorporating tiered remuneration and policy corridor integration demonstrate stronger transmission coherence, while frameworks lacking adaptive safeguards exhibit heightened exposure to deposit substitution risk. Banking sector resilience is reinforced where liquidity backstops, dynamic monitoring, and prudential instruments operate cohesively. Cross-border interoperability introduces systemic externalities that necessitate harmonized supervisory standards to prevent regulatory fragmentation and contagion. The findings advance a governance-centered understanding of digital currency reform, emphasizing that sustainable monetary stability in the digital era depends on multilayered institutional design aligned with macrofinancial discipline.